Farmers Assistance Program Based on Artificial Intelligence (AI) and Big Data - Gao, Qi; Zhang, Liling; Yang, Wanying; Xiao, Jingyi; Xu, Zhiying (International Journal of Computer Science and Information Technology, 2024)
This farmers assistance program aims to build an efficient and intelligent agricultural management system through the deep integration of artificial intelligence (AI) and big data technologies, so as to improve agricultural production efficiency, ensure the quality of agricultural products, promote sustainable agricultural development, and ultimately achieve the goals of increasing farmers’ income and prosperity in rural areas.